SAVI Approach Paper 7: Promoting Gender Equality and Social Inclusion - SAVI (DFID, 2015)
We promote attention to gender equality and social inclusion in all of our engagement with CS groups, the media and SHoAs, and in all of the issues and processes they work on. In all the states we work in, we a lso support partners to focus on some issues and form some partnership s and networks which...